Independence Habituation in the Learning as a Strategy for Improve Student Learning Outcomes During the Covid-19 Pandemic - Ida Lestari; Ruwi Hastuti; Yemima Truly Kaseh (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
The Covid-19 pandemic which has occurred for more than a year in Indonesia has directly and indirectly affected the learning process in universities, one of which is the Intheos Surakarta Theological School. This is due to the lack of intensity of face-to-face meetings between students and lecturers which causes a lack of understanding of the material being taught and students' lack of readiness for distance learning. So that lecturers need to habituate independent learning for each student in addition to so that students are trained to develop their ideas and ideas independently and train students to think critically to face tougher future challenges. For this reason, the author uses a qualitative method approach with case studies and literature studies in order to formulate a habituation strategy for independent learning that is applied by lecturers with various sources that are in accordance with the context of the discussion. From this research, it can be concluded that the more effective the lecturer's strategy in habituating the independent learning of students, the more positive it will be for improving learning outcomes in these courses.